Main directions of development of small business and its performance - Oteshova, A. K. (Journal of Economic Research & Business Administration, 2015)
Entrepreneurship is an important factor in economic development of the enterprise. Entrepreneurship is a necessary link that helps to improve the welfare of the people, to shape a competitive economy, its modernization and diversification. Currently the country has tendency to increase the number of business structures, there is a formation of a civilized modern enterprise that can stand in competition with large and medium-sized businesses and to solve important problems of the national economy. The main factors restraining the development of entrepreneurship in each industry are: the limited financial resources allocated to support businesses, a sharp jump in prices, the low level competitiveness of local entrepreneurs